Ritual, Personhood, and Ecological Ethics: Negotiating Indigenous Ontology and Islam in Molamahu - Badu Pakuna, Hatim; Rostitawati, Tita; Hunowu, Momy; Fadhilah, Amir; Daulay, Pardamean (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article examines Mopo’a Huta, an indigenous ritual practiced by the Molamahu community in Gorontalo, Indonesia, as a site where ecological ethics are enacted through lived religious practice. Existing studies have often framed such rituals either as remnants of pre-Islamic spirituality or as implicit forms of eco-theology. Moving beyond these approaches, this study employs a qualitative descriptive method informed by the concepts of relational personhood and lived religion. Based on participant observation and in-depth interviews, the study shows that Mopo’a Huta is grounded in a relational ontology in which humans, non-human beings (lati-latiyalo), and the natural environment are understood as moral participants in a shared socio-ecological world. Ecological norms emerge not from formal theological reflection but from ritualized relationships and communal practice. Islamic elements incorporated into the ritual reflect ongoing negotiation of religious legitimacy rather than a linear transformation of belief. This study argues that Mopo’a Huta functions as a form of lived religion in which indigenous ontologies and Islamic normativity coexist and are continually renegotiated. By foregrounding ritual practice as the locus of ecological ethics, this study contributes to broader discussions on religion and ecology and indigenous Muslim environmental ethics.